2019
DOI: 10.4103/gmit.gmit_79_18
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ulipristal acetate (Esmya) prior to laparoscopic myomectomy: Help or hindrance?

Abstract: Introduction: The aim of this study was to assess the operative effects, both positive and negative, of pretreatment with ulipristal acetate (UPA) on laparoscopic myomectomy. Materials and Methods: We conducted a retrospective analysis of prospectively collected data from patients who underwent a laparoscopic myomectomy over a 2-year period. Results: A total of 62 patients were included, of which 10 received a 3-month preoperative course of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…[ 2 ] Ulipristal acetate has been introduced as preoperative treatment of patients with large fibroids; however, studies showed that it results in a more technically difficult situation with the potential risk of incomplete resection due to anatomical distortion and unclear cleavage planes. [ 3 ] Although minimally invasive surgery represents the gold standard treatment, laparoscopic myomectomy still requires adequate knowledge of the risk factors for complications, of which the most common is bleeding. The myoma diameter, the number of myomas, and the operative time were found to be significantly associated with blood loss and transfusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Ulipristal acetate has been introduced as preoperative treatment of patients with large fibroids; however, studies showed that it results in a more technically difficult situation with the potential risk of incomplete resection due to anatomical distortion and unclear cleavage planes. [ 3 ] Although minimally invasive surgery represents the gold standard treatment, laparoscopic myomectomy still requires adequate knowledge of the risk factors for complications, of which the most common is bleeding. The myoma diameter, the number of myomas, and the operative time were found to be significantly associated with blood loss and transfusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Larger welldesigned RCTs are needed before conclusions regarding the use of UPA prior to myomectomy procedures may be drawn. Another recent small (n = 10 UPA; n = 52 no pretreatment) retrospective study in the United Kingdom supported the findings of potentially difficult laparoscopic myomectomy with UPA use (Mallick et al 2019).…”
Section: Upa and Surgerymentioning
confidence: 70%
“…UPA is known to have proapoptotic, antifibrotic and antiproliferative effects on uterine fibroids with myometrial sparing (Gaillard et al 1985, Xu et al 2005, Courtoy et al 2015, Donnez et al 2018b. UPA is thought to also effect the fibroid pseudocapsule, which in turn is proposed to make surgical planes challenging to identify and subsequently result in difficult fibroid enucleation (Mallick et al 2019). The pseudocapsule is a fibro-neurovascular structure surrounding the fibroid and separating it from the surrounding myometrium.…”
Section: Upa and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Ulipristal acetate may induce endometrial changes, alter leiomyoma texture, and distort leiomyoma cleavage planes. 19 GnRH agonists too are associated with loss of cleavage planes and incomplete leiomyoma resection. Antiprogesterones (mifepristone/RU486) have also been used but are associated with endometrial changes.…”
Section: Medical Managementmentioning
confidence: 99%